Vadinamųjų kiekio kilmininkų valdymas ir semantika - Labutis, Vitas (Baltistica, 1981)
Genitive of quantity: grammatical government and semanticsGenitives governed by lexical units of quantity and partitive genitives are used in the same syntactical positions, that of the subject and that of the direct object. Although both definite and indefinite quantity can be expressed by lexical units which govern a genitive, grammatical concord is observed only in the expressions of definite quantity (cf. dešimt vyrų, and devyni vyrai), whereas indefinite quantity is expressed by the partitive genitive. However, the use of the genitive is determined not by the opposition of definite quantity vs. indefinite quantity, but by the opposition of part vs. whole. The marked member of the latter opposition is the partitive genitive, the unmarked member being the objective accusative or the subjective nominative.In Lithuanian the part—whole opposition is considerably restricted by the semantic peculiarities of the verb, its actants and the linguistic context. The partitive genitive occurs in the position of the subject only with existential or motion verbs. Yet the partitive genitive is much more frequent in Lithuanian than, for instance, in Russian.As the part—whole opposition is in essence a quantitative opposition, there is no reason why we should speak about the expression of zero quantity or introduce a zero quantitative seme.
Keywords: kiekio kilmininko valdymas; sintaksė; semantika